PEMAKNAAN KOMUNIKASI PANGGUNG PENARI PEREMPUAN PADA TARI RATOH JAROE - Asy’ary, M. Rizki; Dwiningtyas Sulistyani, Hapsari (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2021)
The dilemmatic problems experienced by female dancers of Ratoh Jaroe became the background of this study. On one side, they got the chances to be able to perform publicly. However, on the other side, there are rules about how they should perform. The purpose of this research is to understand the meaning of stage communication by the female dancers of Ratoh Jaroe. This research uses descriptive qualitative methods. Performance studies by Richard Schechner, Cultural Schema Theory by William Gudykunst and Identity Negotiation Theory by Stella Ting-Toomey are the theories used in this research. The results of this research shows that the dancers experienced the stage communication process that occured before, during, and after the performances. Ratoh Jaroe dancers interpreted their dances as the form of entertainment, advice and as the existence of women's identity, religion’s identity and culture’s identity. Furthermore, Ratoh Jaroe emphasizes the existence of female dancers as a form of women power with their roles to express themselves on stage or in public. However, the existence of Ratoh Jaroe as the product of Aceh’ culture requires the dancers to be mindful towards the existing repressions.